Β-Adrenergic receptor structure and function: molecular insights guiding the development of novel therapeutic strategies to treat malignancy. (2nd September 2020) - Ghali, Michael G. Z.; Arborelius, Ulf P.; Yaşargil, M. Gazi
Abstract: β adrenergic receptors mediate effects via activation of G proteins, transactivation of membrane growth factor receptors, or β adrenergic receptor-β arrestin-facilitated scaffold-mediated signaling. Agonist occupancy of the β adrenergic receptor induces desensitization by promoting β adrenergic receptor kinase phosphorylation of the carboxyl terminal domain, facilitating binding of the amino terminal of the β arrestin, which sterically inhibits interactions between β adrenergic receptors and G proteins and induces clathrin-coated pit-mediated receptor endocytosis. Scaffold formation promoted by β arrestin binding to the β adrenergic receptor activates extracellular regulated kinase 1/2 in a manner which elicits cytosolic retention of, and prevents promotion of nuclear transcriptional activity by, mitogen-activated protein kinase. The β adrenergic receptor kinase also interacts with a yet to be determined microsomal membrane protein via high-affinity electrostatic interactions. We evaluate β adrenergic receptor structure, function, and downstream signaling and β arrestin-mediated desensitization, receptor endocytosis, and scaffold-facilitated signal transduction in order to illumine therapeutic strategies designed to modulate these pathways. We trust these approaches may arm us with the capacity to selectively modulate signal transduction pathways regulating cellular proliferation, immunogenicity, angiogenesis, and invasive and metastatic potential implicated in cancer initiation, promotion, and progression.